Developing a Simple Clinical Score for Predicting Mortality and Need for ICU in Trauma Patients. Issue 7 (July 2019) - Haider, Ansab; Con, Jorge; Prabhakaran, Kartik; Anderson, Patrice; Policastro, Anthony; Feeney, James; Latifi, Rifat
Several models exist to predict trauma center need in the prehospital setting; however, there is lack of simple clinical tools to predict the need for ICU admission and mortality in trauma patients. The aim of our study was to develop a simple clinical tool that can be used with ease in the prehospital or emergency setting and can reliably predict the need for ICU admission and mortality in trauma patients. We abstracted one year of National Trauma Data Bank for all patients aged ≥ 18 years. Transferred patients and those dead on arrival were excluded. Patient demographics, injury parameters, vital signs, and Glasgow Coma Scale (GCS) were recorded. Our primary outcome measures were mortality and ICU admission. Logistic regression analysis was performed using three variables (age > 55 years, shock index (SI) > 1, and GCS score) to determine the appropriate weights for predicting mortality. Appropriate weights derived from regression analysis were used to construct a simple SI, age, and GCS (SAG) score, and associated mortality and ICU admissions were calculated for three different risk groups (low, intermediate, and high). A total of 281, 522 patients were included. The mean age was 47 ± 20 years, and 65 per cent were male. The overall mortality rate was 2.9 per cent, and the rate of ICU admission was 28.7 per cent. The SAG score was constructed using weights derived from regression analysis for age ≤ 55 years (4 points), SI< 1 (3 points), and GCS (3-15 points). The median [IQR] SAG score was 21 [18–22]. The area under the receiver operating curve [95% Confidence Interval (CI)] of the SAG score for predicting mortality and ICU admission was 0.873 [0.870–0.877] and 0.644 [0.642–0.647], respectively. Each 1-point increase in the SAG score was associated with 18 per cent lower odds of mortality (odds ratio [95% CI]: 0.822 [0.820–0.825]) and 10 per cent lower odds of ICU admission (odds ratio [95% CI]: 0.901 [0.899–0.902]). The SAG score is a simple clinical tool derived from variables that can be assessed with ease during the initial evaluation of trauma patients. It provides a rapid assessment and can reliably predict mortality and need for ICU admission in trauma patients. This simple tool may allow early resource mobilization possibly even before the arrival of the patient.